2015
DOI: 10.1016/j.earscirev.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Getting over continent ocean boundaries

Abstract: The idea of a simple linear boundary between continental and oceanic crust at extended continental margins is widely recognised to be an oversimplification. Despite this, such boundaries continue to be mapped because of their perceived utility in palinspastic and plate kinematic reconstructions. To examine whether this perception is justified, we review the data and models on which basis continent ocean boundaries are interpreted, and map a set of such interpretations worldwide from more than 150 publications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 178 publications
0
69
1
Order By: Relevance
“…The definition of the Continent-Ocean Boundaries have been made by hand by following "at best" both prominent features in the first derivative of the map of the Earth gravity field model (GRACE GGM02, [10]) and the second derivative in the magnetic anomaly map EMAG2 [11]. The result is however not fundamentally different from other publications as reported by Eagles et al [12], and does not significantly affect the statistical outcomes provided below.…”
Section: /54contrasting
confidence: 32%
“…The definition of the Continent-Ocean Boundaries have been made by hand by following "at best" both prominent features in the first derivative of the map of the Earth gravity field model (GRACE GGM02, [10]) and the second derivative in the magnetic anomaly map EMAG2 [11]. The result is however not fundamentally different from other publications as reported by Eagles et al [12], and does not significantly affect the statistical outcomes provided below.…”
Section: /54contrasting
confidence: 32%
“…Hence, the LaLOC and ECC, independently of the quality of the mapping, cannot be used as markers for plate kinematic restorations. Eagles et al () showed, for instance, that the LaLOCs can never be superposed. Transfer faults cutting the thinned and exhumed mantle domains provide the direction of motion during a stage of deformation, but they do not provide time indications.…”
Section: Hyperextended Rifted Margins: a Kinematic Descriptionmentioning
confidence: 99%
“…The onset of oceanic, or thick oceanic crust of Icelandic type in case of the Walvis Ridge, is at approximately the same distance from shore for all profiles. Besides the disagreement on the location of a COB, Eagles et al (2015) recently challenged the concept of COBs in general. The large uncertainties involved in defining the COB makes it of little use in plate kinematic reconstructions even though the COB is still invoked (Eagles et al, 2015).…”
Section: The Crustal Composition Of the Eastern Walvis Ridgementioning
confidence: 99%